2019
DOI: 10.1371/journal.pone.0225218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two experimental ARDS models in pigs using electrical impedance tomography

Abstract: BackgroundAnimal trials contribute to major achievements in medical science. The so-called lavage model is frequently used to evaluate ventilation strategies in acute respiratory distress syndrome (ARDS) using electrical impedance tomography (EIT). But, the lavage model itself might have systematic impacts on EIT parameters. Therefore, we established an additional experimental model, in which ARDS is caused by intravenously administered lipopolysaccharide (LPS). In this study, we want to examine if EIT measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The animal injury model was developed using LPS, following the procedure described in a previous study by Lutz et al [ 20 ]. However, the LPS dose of 4 mg/kg used in the present study was slightly higher than the dose previously used by other groups [ 21 25 ]. The PS in studies one and three survived to the experiment endpoint, and the PS in trials two and four experienced cardiac arrests before the four-hour experiment endpoint.…”
Section: Resultsmentioning
confidence: 58%
“…The animal injury model was developed using LPS, following the procedure described in a previous study by Lutz et al [ 20 ]. However, the LPS dose of 4 mg/kg used in the present study was slightly higher than the dose previously used by other groups [ 21 25 ]. The PS in studies one and three survived to the experiment endpoint, and the PS in trials two and four experienced cardiac arrests before the four-hour experiment endpoint.…”
Section: Resultsmentioning
confidence: 58%
“…Given the fact that the recruited subjects are all lung-healthy volunteers, the average values and the variations obtained in the study for RVD are not representing the tidal recruitment, as suggested in the clinical studies (e.g. [14,15]).…”
Section: Discussionmentioning
confidence: 99%
“…However, this represents only a minor limitation of the pig as animal model, since a confirmation of the positive anti-thrombogenic and anti-coagulative effect of the porcine EML, in the demanding porcine setting, may indicate that this desired effect might be even more pronounced in the human scenario. However, the pig seems to be the best fitting animal model as multiple porcine lung injury models have also been reported and can be used for BHL assessment [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%